Low Serum Choline Concentrations Are Associated with Worse Cognitive Performance in Subjects with Metabolic Syndrome - Coltell, Oscar (Curr Dev Nutr, 2020)
OBJECTIVES: Choline is an essential nutrient critical for components of the cell membrane, such as choline-containing phospholipids (phosphatidylcholine and sphingomyelin), and in synthesis of the neurotransmitter acetylcholine. Choline has been shown to exert neuroprotective effects, but the association between serum choline and cognitive performance has been scarcely investigated. Our aims are: 1) To study the association between serum total choline, phosphatidylcholine and sphingomyelin with cognitive performance in subjects with metabolic syndrome; and 2) to analyze genetic variants and dietary intake most associated with cholines in this population. METHODS: We analyzed 426 subjects (aged 55–75 y) with metabolic syndrome from the PREDIMED Plus-Valencia Study. Serum total choline, phosphatidylcholine and sphingomyelin were determined by NMR spectroscopy. Cognitive tests, including verbal fluency (both semantic and phonemic fluency) and the Trail Making Test (TMT) (parts A and B), were administered. Candidate gene polymorphisms were determined by array genotyping. Diet was analyzed by validated questionnaires. Multivariate regression models were fitted. RESULTS: Cholines (total, phosphatidylcholine and sphingomyelin) were strongly associated with sex (higher in women; P < 0.001), age (lower at increasing age; P < 0.05) and diabetes (lower in type-2 diabetics; P < 0.01) in a multivariate model. Although the three tested variables presented statistically significant associations with cognition, serum sphingomyelin was the most associated. Thus, in a multivariate model, serum phosphatidylcholine was directly associated with better verbal fluency (P = 0.040 and P = 0.029 for phonemic and semantic, respectively) and inversely associated (lower score mean better performance) with the TMT-A (P = 0.013) and the TMT-B (P = 0.035). In the genetic analysis, we detected several polymorphisms strongly associated with cholines (rs10991629-SLC44A1 with P < 0.005 and rs8068641-PEMT; P < 0.01, among others). We identified several dietary associations as well as gene-diet modulations. CONCLUSIONS: Phosphatidylcholines are associated with better cognitive function and their levels are modulated by diet and genetics. FUNDING SOURCES: Generalitat Valenciana (PROMETEO2017/017) and Spanish Ministry of Science (FPU 18/0,1703).